(untitled) (Research, Society and Development, 2022)
It is extremely necessary to approach preventive maintenance in health care facilities. The maintenance of hospital equipment aims, mainly, at mitigating risks to human health, both for patients and for the professionals involved. The article aims to highlight the effectiveness of preventive maintenance as a safety tool in hospital environments. It is a study based on bibliographic research, covering consultations with journals, institutional repositories and databases of interest to the study. It is justified by the fact that preventive maintenance in EAS favors the economy, once applied in a coherent way it allows the reduction of costs, in this way, the investments now destined for maintenance, can be applied in other areas, allowing the increase of services available to users. When performed properly, it directly influences quality indicators and consequently obtains the privilege of credibility for users who use health facilities. It should be analyzed that the lack of preventive maintenance in health establishments can lead to numerous damages and/or expenses, such as factors related to the insufficient use of hospital equipment and an increase in corrective maintenance. It is essential that the EAS have a Clinical Engineer in their staff responsible for maintenance management, as he will manage the entire technological process in the medical area, aiming at the improvement and quality of the equipment.